Clinical and Prognostic Significance of Tumor-Infiltrating CD8+ T Cells and PD-L1 Expression in Primary Gastrointestinal Stromal Tumors - Sun, Xiangfei; Shu, Ping; Fang, Yong; Yuan, Wei; Zhang, Qiang; Sun, Jianyi; Fu, Min; Xue, Anwei; Gao, Xiaodong; Shen, Kuntang; Hou, Yingyong; Sun, Yihong; et al. (Frontiers in Oncology, 2021)
Purpose: Immunotherapy for gastrointestinal stromal tumors (GISTs) remains a clinical challenge. The present study aimed to explore the clinical and prognostic significance of immune cell infiltration and PD-L1 expression in GISTs. Methods: 507 clinical tissue specimens of primary GISTs were collected for immunohistochemical analysis of immune cell infiltration and PD-L1 expression. Influencing factors of survival were evaluated by Kaplan-Meier analysis. Univariate and multivariate analyses were performed using the Cox regression model. Results: There were significant differences in sex, tumor location, size, mitotic index, NIH risk grade, and cell morphology between different gene mutation types of GISTs. Immune cell infiltration in GISTs mainly involved macrophages and T cells. PD-1 was expressed in 48.5% of the tissue specimens, and PD-L1 expression was detected in 46.0% of the samples. PD-L1 expression was negatively correlated with the tumor size and mitotic index but positively correlated with the number of CD8+ T cells. There were significant differences in the number of CD8+ T cells between different gene mutation types. Wild type-mutant GISTs were enriched with CD8+ T cells as compared with KIT- and PDGFRA-mutant GISTs. The number of CD8+ T cells was higher in non-gastric GISTs. PD-L1 and CD8+ T cells were independent predictors for better relapse-free survival of GISTs. Conclusions: PD-L1 expression is a predictive biomarker for better prognosis of GISTs. Non-gastric GIST patients with wild-type mutations may be the beneficiaries of PD-1/PD-L1 inhibitors.